Size-selective adsorption of methyl orange using a novel nano-composite by encapsulating HKUST-1 in hyper-crosslinked polystyrene networks. (20th May 2018) - Shen, Jiachun; Wang, Xuzeng; Zhang, Limin; Yang, Zhen; Yang, Weiben; Tian, Ziqi; Chen, Jianqiang; Tao, Tao
Abstract: A novel nano-composite adsorbent, NDA88-Cu, was successfully prepared by immobilization of HKUST-1 (a typical MOF) into hyper-crosslinked polystyrene networks NDA88 (loading ratio: 350 mg of MOFs with particle size in the range of 10–100 nm per gram of polystyrene networks). The adsorbent demonstrated advantages of improved stability without leakage of metal ions during the adsorption assays compared to HKUST-1 itself, and faster solid-liquid separability than NDA88 or HKUST-1, which could effectively avoid the shortcomings of MOFs like potential secondary pollution and poor performance in separation. When applied for the adsorption of five typical dyes with various charges and molecular sizes (cationic: methylene blue (MB) and rhodamine-B (RhB); anionic: methyl orange (MO), methyl red (MR) and acid green (AG25)), NDA88-Cu worked for the removal of anionic ones but showed almost no adsorption capacity towards cationic ones because of Donnan membrane effect exerted by the host NDA88. For the three anionic dyes, NDA88-Cu displayed not only heightened adsorption capacity towards MO (398.8 mg/g), but also size-selective uptake of MO from solution with mixed dyes. The adsorption capacity remained high levels after ten adsorption-desorption cycles. Mechanism investigations, including macroscopic physico-chemical analyses, instrumental investigation and density functional theoretical calculations, gave direct evidences of the size selectivity of NDA88-Cu with hierarchical pore structure. Coordination effect of Cu-MO predominated, while π-π interactions and electrostatic attraction also took place, in the fixing of MO onto the adsorbent. The current work provides a useful idea for the separation of contaminants with similar structure from water, and acts as a good case for the application of nanotechnology in wastewater treatment and resource recovery. Graphical abstract: Image 1 Highlights: NDA88-Cu has enhanced size-selective adsorption of MO from mixed-dye solutions. The adsorbent NDA88-Cu has improved stability and solid-liquid separability in water. Mechanism of size-selectivity is clarified by experimental study and DFT calculation.